Effects of 8-Week Anaerobic Gymnastics Training on Weight Loss and Related Growth Factors in Obese Children: A Clinical Trial - Vahid Saleh; Roghayyeh Afroundeh (Mazandaran University of Medical Sciences, 2022)
Background: Overweight and obesity are prominent threats to pediatric health. The prevalence of childhood obesity has dramatically been increasing worldwide.  Objectives: In this study, we analyze the effects of 8-week anaerobic gymnastic training on weight loss and related growth factors in obese children. Methods: In this clinical trial study, 30 obese elementary gymnasts in the age range of 8 to 12 years were randomly divided into control (n=15) and experimental (n=15) groups. The experimental group performed 45 minutes of anaerobic gymnastics training. Anthropometrical and body composition characteristics, maximal oxygen consumption, and the levels of brain-derived neurotrophic factor (BDNF), and vascular endothelial growth factor were measured before and after 8 weeks of training. Results: At the baseline, there were no significant differences for any of the dependent variables between the two groups (P≥0.05). After 8 weeks of training, values of weight, waist-hip ratio, body fat percentage, body fat weight, lean body weight, and maximal heart rate decreased significantly (P<0.05) while maximal oxygen consumption and BDNF increased significantly (P<0.05). Conclusions: We concluded that weight loss because of anaerobic gymnastic training may lead to a high serum concentration of BDNF. High BDNF may help in maintaining a reduced weight after intervention for obesity and may increase fat oxidation. The inhibitory effects of weight loss on vascular endothelial growth factor may have abolished the stimulatory effects of exercise and prevented a significant increase in the vascular endothelial growth factor level.